A Critical View of Current State of Phytotechnologies to Remediate Soils: Still a Promising Tool?. (4th January 2012) - Conesa, Héctor M.; Evangelou, Michael W. H.; Robinson, Brett H.; Schulin, Rainer
Abstract : Phytotechnologies are often shown as an emerging tool to remediate contaminated soils. Research in this field has resulted in many important findings relating to plant and soil sciences. However, there have been scant private and public investments and little commercial success with this technology. Here, we investigate the barriers to the adoption of phytotechnologies and determine whether it is still a fertile area for future research. The terminology used in phytotechnologies includes a confusing mish-mash of terms relating to concepts and processes increasing the difficulty of developing a unique commercial image. We argue that the commercial success of phytotechnologies depends on the generation of valuable biomass on contaminated land, rather than a pure remediation technique that may not compare favourably with the costs of inaction or alternative technologies. Valuable biomass includes timber, bioenergy, feedstock for pyrolosis, biofortified products, or ecologically important species.